Determinants of Digital Banking Usage: The Role of Service Features, Electronic Word of Mouth, and Brand Image in the Use of BRImo Mobile Banking Application - Nana Soviana; Jumi Jumi; Taviyastuti Taviyastuti (International Journal of Marketing and Digital Creative, 2026)
The rapid growth of digital banking has intensified competition among financial institutions to attract and retain mobile banking users. In this context, understanding the factors that influence customers’ decisions to use digital banking applications has become increasingly important. However, previous studies have primarily focused on technological perceptions, while limited attention has been given to the combined role of service features, electronic word of mouth (eWOM), and brand image in shaping digital banking use. This study aims to examine the influence of service features, eWOM, and brand image on the decision to use the BRImo mobile banking application. The research uses a quantitative explanatory design and collects primary data from BRImo users through an online survey. A total of 115 valid responses were analyzed using multiple linear regression. The findings reveal that service features, electronic word of mouth, and brand image significantly influence the decision to use the BRImo application. Among these factors, service features demonstrate the strongest impact, indicating that usability, reliability, and feature integration play a crucial role in shaping digital banking use. This study contributes to the extension of the Technology Acceptance Model (TAM) by integrating marketing related factors such as eWOM and brand image into the technology use framework. The findings also provide practical insights for banks in improving digital customer engagement through application usability, online reputation management, and strategic brand positioning.